Migraine and angiotensin-converting enzyme association in Turkish patients - Cakmak, EA; Cataloluk, O; Yoldas, T; Arslan, A; Herken, H; Barlas, O; Yigiter, R (Vsp Bv, 2003)
Although there are an increasing number of publications claiming involvement of the ACE I/D polymorphism in mood disorders, none of them has been able to show any linkage between allele and genotypical distributions and psychiatric disorders. We investigated the possibility of association between ACE I/D polymorphism and migraine in 200 migraineurs and 231 control subjects of Turkish origin. No association was found between ACE I/D polymorphism and migraine. However, the results of our study suggested that the DD genotype is more frequent in men than in women.
Keywords: migraine; ACE; PCR; genetics